2017
DOI: 10.9790/1959-0601047585
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Wellbeing and Communication Styles among Medical-Surgical Nursing Students

Abstract: Abstract:The more psychologically healthy the nursing students are, the more likely they will be productive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(15 reference statements)
0
3
1
Order By: Relevance
“…Students' wellbeing could likely be a function of their socioeconomic status, and not related to communication. This contradicts the findings of Brinia et al (2022) and Ramadan and Yakout (2017) whose studies showed a positive and significant relationship between communication and wellbeing.…”
Section: Communicationcontrasting
confidence: 89%
See 1 more Smart Citation
“…Students' wellbeing could likely be a function of their socioeconomic status, and not related to communication. This contradicts the findings of Brinia et al (2022) and Ramadan and Yakout (2017) whose studies showed a positive and significant relationship between communication and wellbeing.…”
Section: Communicationcontrasting
confidence: 89%
“…belonging(McIntyre et al 2018;Šeboková and Uhláriková 2017;Tholen et al 2022), stress(Bye, Muller, and Oprescu 2019;Tholen et al 2022), and wellbeing(Brinia et al 2022;Ramadan and Yakout 2017). The following hypotheses were testing the relationship between communication and the three variables.…”
mentioning
confidence: 99%
“…This result was contradicted with Tiwari, Imam and Nagar et al (2021) who found that (86,8%) of the study subject their father education was illiterate and (15,8%) had governmental job. This result was also contradicted with Ramadan and Ahmed (2015) who found that more than half of the participants 60.0% father and mother educational level of the intervention group was secondary education.…”
Section: Discussionmentioning
confidence: 59%
“…These findings align with those of Abd El-Aziz and Sorour (2013) , who similarly observed intermediate decision-making abilities among nursing students in their study. Furthermore, according to Abou Ramadan and El-Demerdash (2017) , the majority of nursing students have a moderate degree of CDM.…”
Section: Discussionmentioning
confidence: 99%